Commissioning and cryogenic performance of the UKRI STFC Daresbury Vertical Test Facility for jacketed SRF cavities. Issue 1 (1st May 2022) - May, A J; Pattalwar, S; Mason, D; Middleman, K; Pendleton, M D; Smith, P A; Wilde, S; Akintola, A; Bainbridge, A; Buckley, R; Collier, G; Corlett, P; et al.
Abstract: A novel vertical test facility has been developed at the STFC Daresbury Laboratory. The cryostat is designed to test 3 jacketed superconducting RF cavities in a horizontal configuration in a single cool-down run at 2 K. The cavities are cooled with superfluid helium filled into their individual helium jackets. This reduces the liquid helium consumption by more than 70% in comparison with the conventional facilities operational elsewhere. The facility has now completed commissioning successfully and moved into a 2-year program to qualify 84 high-beta SRF cavities for the ESS (European Spallation Source) as part of the UK's in-kind contribution. This paper reports on the commissioning program, along with a detailed discussion of the cryogenic operations and performance of the facility, including that of the cryoplant.